Perception of employers and employees towards artificial intelligence in innovative HRM - MONICA, DR. BENITA. S.; VYAS R, MS. SHRUTI (The journal of contemporary issues in business and government, 2020)
Artificial Intelligence is an innovative technology that permits computers to learn and suggest activities dependent on recently gathered data or information. AI can introduce open doors for dominating new abilities and acquiring extra time, permitting HR experts to extend their present parts to be more strategic areas inside their enterprise. Artificial intelligence is adding an individual touch to the new contestants and is enlarging the onboarding encounters of HR by making altered administrations. The sample for conducting this study is collected from the Automobile industry (2 & 3 Wheelers dealership) and the data is collected from the low, middle and top-level management. Tool used to analyze the data collected is Analysis of Variance (Anova), a statistical test of whether two or more population means are different, and therefore generalizes the t-test beyond two means. Results for the test conducted provided that there is no significant difference between the age and the described factors. This study will be useful for the HR professionals, who believe that implementing AI in the field of HR will replace humans and will help them with spending more time for their strategic fields rather than spending time for less prioritized HR functions.